Piscicidal effects of Albizzia procera (Benth) seeds, Swientenia mahagoni (Jacq) and Azadirachta indica (A. juss) seed kernels and Camellia sinensis (Wiild) seed cake extracts on Oreochromis mossambicus (Peters) and Channa punctatus (Bloch.) - Nasiruddin, Munra; Azadi, Mohammad Ali; Begum, Nasima (Chittagong University Journal of Biological Sciences, 2013)
Piscicidal effects of distilled water and fifty percent ethyl alcohol extracts of Albizzia procera seeds, Swietenia mahagoni and Azadirachta indica seed kernels and Camellia sinensis seed cake were bioassayed upon Oreochromis mossambicus and Channa punctatus under normal laboratory conditions. Due to the toxic effects, the piscicide treated fishes showed irritability, excitement and gradual loss of balance. Mortality in both the species showed dose dependent increase with increasing concentrations. From the LC50 values, the relative toxicities of the plant extracts for both the fishes were found to be A. procera seeds > C. sinensis seed cake > S. mahagoni seed kernels> A. indica seed kernel extracts. The degree of tolerance of the test fishes to any of the two extracts was in the order C. punctatus > O. mossambicus. DOI: http://dx.doi.org/10.3329/cujbs.v4i1.13385 The Chittagong Univ. J. B. Sci.,Vol. 4(1&2):41-52, 2009